Vehicle routing and scheduling of demand-responsive connector with on-demand stations. (June 2017) - Shen, Jinxing; Yang, Shuqian; Gao, Xuming; Qiu, Feng
As an important supplement of conventional fixed-route public transit, flexible transit services draw more attention in low-demand areas recently. Demand-responsive connector is one of those flexible transit services and has already been operated as feeder transit in some cities. This article concentrates on the vehicle routing operation of the demand-responsive connector system with on-demand stations. A two-stage routing model is proposed to minimize the system cost, considering both the service provider and riders, and two solution algorithms are proposed and compared for the routing model. A simulation experiment based on a real-life case study in Nanjing city is conducted to demonstrate the applicability of the proposed vehicle routing model. The results demonstrate that our vehicle routing modeling and optimized algorithm can confidently handle the daily operation of demand-responsive connector services with on-demand stations.